Extração de carotenóides totais e ß-caroteno por ultrassom no resíduo de indústria de polpa de goiaba (Psidium guajava L) - Santos, Thatiana Santana (2013)
This work reports the extraction ß-carotene and total carotenoids in the residue of the guava pulp industry by Soxhlet and ultrasound. The Soxhlet technique was evaluated from the solvent: dichloromethane, methanol and hexane, and drying process: freeze-drying and convective drying. The solvents dichloromethane showed the best yield ß-carotene and total carotenoids and the drying by freeze was most favorable. Ultrasound extraction was evaluated: relation mass/solvent, temperature, time and power extraction device. The better extraction condition for maximum yield of ß-carotene by ultrasound was 20 minutes, at a sample to solvent radio 1:70 (g mL-1), power 154 W and temperature 30°C. The results showed that ultrasound obtained it highest ß-carotene yield (693,16 µg 100 g-1) in 20 minutes only, while Soxhlet obtained low yield (494, 9 µg 100g-1) in 8h. For total carotenoids the Soxhlet extraction obtained a yield of 6693,4 µg 100 g-1, in the ultrasound obtained the better yield (9912,28 µg 100 g-1) in the power 92,4W.